The Pocket Essential American Civil War - Davies, Phil (Pocket essentials., 2001)
A concise and well-informed introduction to the most traumatic and bloodiest war in American history. Examines the deep-rooted causes of the war and the political and military leadership of the North and the South. Recounts the events that led from the early battles through the terrible confrontations at Gettysburg and Vicksburg to the South's final surrender at Appomattox in 1865. Complete with maps, chronology and details of further resources, this is the ideal introduction to the war that shaped American history.